Dioscin Promotes Prostate Cancer Cell Apoptosis and Inhibits Cell Invasion by Increasing SHP1 Phosphorylation and Suppressing the Subsequent MAPK Signaling Pathway - He, Shuyun; Yang, Jinrui; Hong, Shaobo; Huang, Haijian; Zhu, Qingguo; Ye, Liefu; Li, Tao; Zhang, Xing; Wei, Yongbao; Gao, Yunliang (Frontiers in Pharmacology, 2020)
Dioscin possesses antioxidant effects and has anti-cancer ability in many solid tumours including prostate cancer (PCa). Nevertheless, its effect and mechanism of anti-PCa action remain unclear. The tyrosine protein phosphatase SHP1, which contains an oxidation-sensitive domain, has been confirmed as a target for multicancer treatment. Further studies are needed to determine whether dioscin inhibits PCa through SHP1. We performed in vitro studies using androgen-sensitive (LNCaP) and androgen-independent (LNCaP -C81) cells to investigate the anticancer effects and possible mechanisms of dioscin after administering interleukin-6 (IL-6) and dihydrotestosterone (DHT). Our results show that dioscin inhibited cell growth and invasion by increasing SHP1 phosphorylation [p-SHP1 (Y536)] and inhibiting the subsequent P38 mitogen-activated protein kinase signalling pathway. Further in vivo studies confirmed that dioscin promoted caspase-3 and Bad-related cell apoptosis in these two cell lines. Our research suggests that the anticancer effects of dioscin on PCa may occur through SHP1. Dioscin may be useful to treat androgen-sensitive and independent PCa in the future.